Tea Tree Oil Terpinen-4-ol Protects Gut Barrier Integrity by Upregulation of Tight Junction Proteins via the ERK1/2-Signaling Pathway - Yong, Yanhong; Fang, Biao; Huang, Yingxin; Li, Junyu; Yu, Tianyue; Wu, Lianyun; Hu, Canying; Liu, Xiaoxi; Yu, Zhichao; Ma, Xingbin; Gooneratne, Ravi; Li, Sidong; et al. (Frontiers in Nutrition, 2022)
Tea tree oil (TTO) has potent antioxidant, antibacterial, and anti-inflammatory activity and is commonly used in skincare products. However, it remains to be elucidated whether TTO can protect the gut barrier from damages in inflammatory bowel disease (IBD) patients. Herein, we report the impact of terpinen-4-ol (TER, the primary constituent of TTO) on lipopolysaccharide (LPS)-induced impairment of intestinal epithelial barrier functions in intestinal porcine epithelial cell lines (IPEC-J2) and dextran sulphate sodium (DSS)-induced IBD in mice. TER protected against LPS-induced damages in IPEC-J2 cells in vitro and attenuated DSS-induced colitis in vivo. TER promoted the expression of tight junction (TJ) protein in vitro and in vivo and attenuated the LPS-induced upregulation of ERK phosphorylation in IPEC-J2 cells. Following ERK-pathway inhibition, TER did not promote the expression of TJ protein, denoting that the ERK signaling pathway mediates the upregulation of TJ proteins. Our data suggest that TER might have the potential application in treating IBD.